A dielectrophoretic method of discrimination between normal oral epithelium, and oral and oropharyngeal cancer in a clinical setting. Issue 15 (7th August 2015) - Graham, K. A.; Mulhall, H. J.; Labeed, F. H.; Lewis, M. P.; Hoettges, K. F.; Kalavrezos, N.; McCaul, J.; Liew, C.; Porter, S.; Fedele, S.; Hughes, M. P.
<x xml:space="preserve">Abstract</x> DEP has the potential to be developed into a low-cost, rapid tool for the early identification of oral cancer in primary care.